Catalytic wet peroxide oxidation of 4-nitrophenol with new pillared clays prepared from the natural material extracted in deposits of Kazakhstan - Kalmakhanova, M.S.; Massalimova, B.K.; Diaz de Tuesta, J.L.; Kulazhanova, A.S.; Kulbaeva, D.A.; Kantarbaeva, S.M. (KSU Publ., 2018)
Natural resources are among the main wealth of the Republic of Kazakhstan, including abundant and cheap natural clays in the southern and northern region of the country. The chemical industry in Kazakhstan has been developing well in recent years and there is an urgent need to find solutions for the treatment of the wastewaters they generate. Composite adsorbents based on natural and pillared clays modified with metal ions have significant prospects for practical use in various fields, such as wastewater treatment, oxidation of organic pollutants, and adsorption of light organic gases. Development of destructive methods based on deep transformations of organic pollutants is considered as a promising direction. Oxidation-reduction reactions activated by various physicochemical reagents allow ensuring complete destruction of hardly oxidizable organic substances and transferring them to safe low-molecular compounds. This work aims to explore natural clays in the synthesis of low-cost pillared clays to be used as catalysts in oxidation technologies for the treatment of wastewaters. Pillared clays with Zn/Fe cations have been prepared from natural clays of Kazakhstan deposits and assessed as catalysts for the catalytic wet peroxide oxidation of 4-nitrophenol that was followed by measuring 4-nitrophenol, H2O2 and the total organic carbon at 398 K. The degradation efficiency of 4-nitrophenol was 100 % with Karatau and Kokshetau Zn-Fe pillared clays and total organic carbon removal was 66 % with Karatau Zn-Fe pillared clay after 2h, considering reaction runs carried out with 5 g/L of pillared clays and at a temperature of 50 ºC.
Қазақстандағы елді мекендеріндегі табиғи материалдан алынған жаңа бағаналы сазбалшықтардың көмегімен 4-нитрофенолды ылғалды каталитикалық сутегі асқынтотықпен тотықтыру
Каталитическое мокрое пероксидное окисление 4-нитрофенола с новыми столбчатыми глинами, полученными из природного материала, добытого на месторождениях Казахстана
Keywords: natural clays; pillared clays; catalytic oxidation; 4-nitrophenol; wastewater; TOC; CWPO; degradation